Tribological study of A1 based natural fibre reinforced composite brake pad materials - Maleque, Md. Abdul; A. R., Zamani; R. J., Talib (2011)
Tribological behavior of Al–based natural fiber reinforced composites (NFC) brake pad materials was studied using CHASE Dynamometer machine in accordance with Society of Automotive Engineer standard procedure SAE J661. In this study, the NFC sample with a size of 25 mm x 25 mm x 6 mm was fabricated using powder metallurgy route for friction and wear test. Five different laboratory formulations such as S1, S2, S3, S4 and S5 were prepared with varying coir fiber contents from 0, 5, 10, 15, and 20 % volume fractions along with binder, friction modifier, abrasive material and solid lubricant. Characterization techniques such as SEM and CHASE Dynamometer machine are used to characterize and analyze the properties of brake pad materials. Out of the five formulations, S2 and S3 showed better properties in terms of wear and friction compared to others. Formulation S2 exhibits better thermal stability and wear resistance. The microstructure reveals uniform distribution of constituents materials along with the coir fiber in S2, S3 and S4. It can be concluded that S2 and S3 showed better tribological properties compared to other formulations. Hence, natural coir fiber can be used as a candidate fiber or filler material for the mass-scale fabrication of asbestos-free brake pad without any harmful effect. Keywords: Coir fiber, Natural fibre Composite (NFC), Friction coefficient